(3GdJegjO deG aj GdehWC ef GdeYGfi hGdCSGfjOs - (3jhSa Hf YHO Gddg Hf YHO GdHQ GdfeQj GdbQWHj GdeGdcj, GHf YHO GdHQ , CHh YeQ , J (B463 (3g` s; (3GdGeGe eGdc , eGdc Hf CfS Hf eGdc GdGUHMj,J (B179 (3g` s
(3ChdgG (B:s
(3YHO GdQMef Hf OGO hCeG MOjK YHO Gddg Hf YeQ aMOKfG Gf YHO GdQMef Hf YHO Gddg s
(3BNQgG (B:s
(3Ydi Gf ddEeGe Gf jSFd ddeSGcjf Ydi GdUObGJ hdSGFd GdeSdejf Ydi HjJ GdeGd dCfg cGdhUi ced GdSaQ GdKGfi ef cJGH GdJegjO s
(3GdfSNI HgG MhGTs
(3fSNI CNQis
(3bQf GdfSN (B:s
(3GdbQf GdSGHYs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B257 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B8 - (3U (B168s
Keywords: (3GdMOjK h GdeUWdMs